ANALISIS IMPLEMENTASI MANAJEMEN KEUANGAN BERBASIS TEKNOLOGI PADA UMKM DI KOTA TANGERANG SELATAN - Supatmin, Supatmin (Yayasan Education and Social Center, 2024)
This study investigates the factors influencing the adoption of financial technology (fintech) among Small and Medium Enterprises (SMEs) in South Tangerang, Banten. Using a qualitative approach, data were collected through in-depth interviews and observations with SME owners, fintech service providers, and experts in economics and finance. The findings reveal that financial literacy, infrastructure limitations, and resistance to change are the primary barriers to fintech adoption. Low financial literacy significantly hinders SMEs’ understanding of fintech benefits. Additionally, inadequate technological infrastructure in certain areas complicates access to digital financial services. However, SMEs that have adopted fintech report improved financial management and operational efficiency. The study concludes that enhancing financial literacy, providing better infrastructure, and offering targeted training are essential to fostering greater fintech adoption. Government and fintech providers can play a crucial role in supporting SMEs in overcoming these challenges